Smart health costing system - Alam, Smansaf (Wasit Journal of Computer and Mathematics Science, 2022)
Smart Health Costing provides the benefits of streamlined operations, improved management and control, superior patient care, strict cost control and improved productivity. HMS is powerful, flexible and easy to use and has been designed and developed to deliver real, conceivable benefits to hospitals. Most importantly, it is backed by reliable and dependable support. The Hospital Management System project is based on database, oriented and networking techniques. Because there are many areas where we keep records in the database we use SQL SERVER which is one of the best and easiest software to keep our information. This project uses C# as a front-end program which is object oriented programming and has a connection to SQL SERVER. The smart health costing system is specifically designed to meet the specific requirements of medium and large sized hospitals around the world. All required modules and features are specifically designed to suit your requirements. It covers all required modules right from patient registration, medicine details, doctor, wards, administrator, patient appointment, bill payment, discharge details etc. The human body is a very complex and developed structure consisting of millions of tasks. Man has understood all these complex functions, part by part from their research and experiments. With the advancement of science and technology, medicine has become an integral part of research. Gradually, medical sciences became a completely new branch of science. As of today, the health sector consists of medical institutions, such as hospitals, hospitals, etc., research and development institutions and medical colleges. Thus the health sector aims to provide the best medical facilities to the general public.
Keywords: smart health, health cost, Sql, Database